Models in Engineering Design as Decision-Making Aids. Issue 2 (4th May 2022) - Eckert, Claudia; Hillerbrand, Rafaela
Abstract : Although models and modeling are central to engineering design, they have received much less attention than models or modeling in the philosophy of science. This paper draws on insights from the philosophical literature on models in science to elucidate models in engineering. Many of the apparent differences are a matter of degree. Models in engineering design do not function solely as representational or more general epistemic vehicles. Rather, models are central to facilitating decision making. This seems to be less pronounced in laboratory practices for scientific research than in engineering design. In engineering, often only the designers understand and determine the relation between the model and its target system. In this, they serve as truth makers and truth keepers. This social process of design is essential to understanding the role of models and modeling from a meta perspective, but is also relevant to engineer when models are reused. A better understanding of these roles can help to illuminate the roles of models in engineering. To illustrate these points, this paper uses the design of a 3D printed kayak as an example that shows how even a fairly modest engineering design project requires the creation of a multitude of different models.